Robotics: Science and Systems XIV 2018
DOI: 10.15607/rss.2018.xiv.068
|View full text |Cite
|
Sign up to set email alerts
|

Autonomous Thermalling as a Partially Observable Markov Decision Process

Abstract: Abstract-Small uninhabited aerial vehicles (sUAVs) commonly rely on active propulsion to stay airborne, which limits flight time and range. To address this, autonomous soaring seeks to utilize free atmospheric energy in the form of updrafts (thermals). However, their irregular nature at low altitudes makes them hard to exploit for existing methods. We model autonomous thermalling as a POMDP and present a recedinghorizon controller based on it. We implement it as part of ArduPlane, a popular open-source autopil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Reddy et al [15], like Wharington [18], present a proof-of-concept approach in simulation, but utilize the much more detailed thermal simulation based on Rayleigh-Bénard convection. Guilliard et al [10] compare ArduSoar to another thermalling controller, POMDSoar, that generates thermalling trajectories by approximately solving a POMDP and thereby explicitly plans for thermal exploration. In turbulent conditions of Guilliard et al [10]'s experiments POMDSoar outperformed ArduSoar, but critically relied on accurate estimates of several additional airframe-specific parameters to do well, making POMDSoar more involved to use in practice.…”
Section: Related Workmentioning
confidence: 99%
“…Reddy et al [15], like Wharington [18], present a proof-of-concept approach in simulation, but utilize the much more detailed thermal simulation based on Rayleigh-Bénard convection. Guilliard et al [10] compare ArduSoar to another thermalling controller, POMDSoar, that generates thermalling trajectories by approximately solving a POMDP and thereby explicitly plans for thermal exploration. In turbulent conditions of Guilliard et al [10]'s experiments POMDSoar outperformed ArduSoar, but critically relied on accurate estimates of several additional airframe-specific parameters to do well, making POMDSoar more involved to use in practice.…”
Section: Related Workmentioning
confidence: 99%
“…The other common autonomous soaring strategies include mechanical energy-based feedback control and the extended Kalman filter-based method (Kahn, 2017; Notter et al , 2020). Furthermore, the Markov Decision Process had been introduced in the autopilot to build a simulator for a specific thermal (Guilliard et al , 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Experimental tests using high-fidelity numerical simulations of real wind fields showed that the energy map method achieved good results in solving the problem of long-distance flight in unmanned aerial vehicles. Guilliard et al [13] dealt with the problem of the autonomous balanced utilization of updrafts and environmental mapping as a partially observable MDP, which was based on predicted trajectories when given actual system states rather than generating Markov tuples offline. The researchers further applied this algorithm to the popular open-source autopilot ArduPlane and compared it with existing alternative algorithms in a series of real-time flight experiments.…”
Section: Introductionmentioning
confidence: 99%